2021
DOI: 10.1021/acs.energyfuels.1c01016
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Effect of CH4 on NH3 Combustion in an O2/N2 Environment Via ReaxFF

Abstract: At a time of striving for CO2-free power, NH3 becomes a potential energy storage carrier fuel from renewable sources. The reaction molecular dynamics (ReaxFF-MD) method was used to study the effect of CH4 reactivity on NH3 oxidation in an O2/N2 environment. The conversion process of combustion intermediates in the combustion process is explored. Under fuel-rich, stoichiometric, and fuel-lean conditions, at a temperature of 2400–3200 K, mixed combustion of NH3 and CH4 with different concentration ratios is simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Therefore, cofiring ammonia with more reactive fuels, such as methane, hydrogen, or biogas, is an effective method to promote flame instability. For fundamental properties, Xiao et al experimentally and numerically studied the ignition delay time of NH 3 /CH 4 mixtures under gas turbine conditions . The results showed that ignition delay times were significantly decreased when the pressure increased.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cofiring ammonia with more reactive fuels, such as methane, hydrogen, or biogas, is an effective method to promote flame instability. For fundamental properties, Xiao et al experimentally and numerically studied the ignition delay time of NH 3 /CH 4 mixtures under gas turbine conditions . The results showed that ignition delay times were significantly decreased when the pressure increased.…”
Section: Introductionmentioning
confidence: 99%